If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -48 = 6x + -1x + 2 Reorder the terms: -48 = 2 + 6x + -1x Combine like terms: 6x + -1x = 5x -48 = 2 + 5x Solving -48 = 2 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -48 + -5x = 2 + 5x + -5x Combine like terms: 5x + -5x = 0 -48 + -5x = 2 + 0 -48 + -5x = 2 Add '48' to each side of the equation. -48 + 48 + -5x = 2 + 48 Combine like terms: -48 + 48 = 0 0 + -5x = 2 + 48 -5x = 2 + 48 Combine like terms: 2 + 48 = 50 -5x = 50 Divide each side by '-5'. x = -10 Simplifying x = -10
| x^3-3x^2-2a+5=0 | | 2(p+5)+5=p-14 | | 0.000769= | | 8b-20=12 | | 7-(q-4)= | | -9+4x-7x=-39 | | 34-p=10 | | x-10-7x=62 | | 10=2x^2-7x+6 | | -10x-6=-4x+12 | | 9d-4=7d+5 | | 15x+25=2x-1 | | -2-2x=-16 | | 24(x-6)= | | Y=3sin(x^2+1) | | x-33=2x | | 2x-6=-30 | | 8(2x-3)=32 | | S^2+13=10s | | Z^2-(3+I)z+(2+I)=0 | | y=e | | 5-4(x+2)=2x+9 | | 5(y-2)-y=3y+7 | | 2a^2-a=3 | | 13(9-2x)=x+1 | | 7=14a | | X^2-10x+25=225 | | 6x=x-6 | | 7x*8x=56 | | 4x+89=581 | | g(-2)=3x^2-4x+1 | | g(x)=3x^2-4x+1 |